2013
DOI: 10.1080/13607863.2013.837145
|View full text |Cite
|
Sign up to set email alerts
|

Meditation-based interventions for family caregivers of people with dementia: a review of the empirical literature

Abstract: Objectives: Providing care for a family member with dementia is associated with increased risk of adverse mental health sequelae. Recently, interventions utilising meditation-based techniques have been developed with the aim of reducing psychological distress among dementia caregivers. The present review aimed to critically evaluate the extant empirical literature in order to determine: (1) whether meditation-based interventions can reduce depression among dementia caregivers and (2) whether meditation-based i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…Although interventions to reduce caregiver burden, improve caregivers’ ability to cope, increase their self-efficacy, and enhance their quality of life (Northouse et al, 2010, Hurley et al, 2014, Lavretsky et al, 2013) exist, identifying objective ways to document their impact on the physical health of the caregiver is likely required for the systematic uptake into policy and practice. The purpose of this study was to correlate the self-reported burden and distress with objective neuroendocrine and immune measures of the stress response to operationalize the impact on the caregiver’s health.…”
Section: Resultsmentioning
confidence: 99%
“…Although interventions to reduce caregiver burden, improve caregivers’ ability to cope, increase their self-efficacy, and enhance their quality of life (Northouse et al, 2010, Hurley et al, 2014, Lavretsky et al, 2013) exist, identifying objective ways to document their impact on the physical health of the caregiver is likely required for the systematic uptake into policy and practice. The purpose of this study was to correlate the self-reported burden and distress with objective neuroendocrine and immune measures of the stress response to operationalize the impact on the caregiver’s health.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that carer support programmes that incorporate principles of risk management (Department of Health, ), or interventions that utilise meditation‐based techniques to help address anxiety, may be beneficial. Such interventions, including elements of mindfulness meditation, have recently been evaluated (Hurley et al ., ) and found to reduce carer burden in the short‐term, but their long‐term benefits have yet to be demonstrated.…”
Section: Discussionmentioning
confidence: 97%
“…Findings based on only one intervention study within each review do not appear in Table 2; thus this meta-review focuses on findings with a certain degree of replication, or lack of, at the time of publication of each of the reviews. The effectiveness of psychoeducation was addressed in 14 reviews [12,23,28,29,34,37,41,49,51,53,58,62,66,70], counseling and psychotherapy -10 reviews [12,22,29,32,36,37,53,57,58,66], occupational therapy (OT) interventions -2 reviews [16,66], mindfulness-based interventions (e.g., mantra repetition, meditation, yoga, mindfulness-based stress reduction) -5 reviews [21,22,33,38,43], support interventions (e.g., support groups, mobilizing informal networks) -5 reviews [12,24,49,59,62], communication skills training -3 reviews [27,47,48], respite -6 reviews [12,22,45,63,65,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Among the 43 reviews that analyzed burden (including measures of overload, stress and behavioral bother), over half (k = 28) provided support for intervention effects. Burden was found to be reduced by psychoeducation [12,34,37,51,53,58,66], counseling/psychotherapy [12,32,36,53] OT interventions, [16], mindfulness-based interventions [21,33,38], communication training [47], respite/ day care [12,63], home support [20], care coordination/ case management [15,53], physical activity interventions [50], multicomponent interventions [14,31], dyadic interventions [39], technology-based interventions [17,28,46,51,54], and miscellaneous or intervention programs in general [12,19,35,53,61].…”
Section: Burdenmentioning
confidence: 99%
See 1 more Smart Citation